New Solutions Pro-Family under Polish Law and the European - Ziółkowska, Krystyna (Studia Warmińskie, 2014)
The power in the rule of law is to be exercised by the governing bodies, which are provided for in the constitutional arrangements and in special provisions. The government together with the Prime Minister shall exercise the power in the state, by its political program is realized. The provisions regarding family policies that are entered in the Labor Code have to step up to the target, the attractiveness of the enlargement of the family, the starting of closer relationships between parents, greater involvement of the father in child rearing. Apart from all the favorable privileges, employers will continue to set the objection young women who are not working in the labor market throughout the year (if they make such a decision ). If such parental powers contribute to the enlargement of the family? If the woman who returns from an extended maternity leave, have a labor warranty? So give asked questions in this regard impetus to deeper reflection and reflection on the role of the family in the state.